Factors Influencing Failure of Reading - Anis Mawati (Register Journal, 2008)
The objective of this research are: to find out the forms of failure of reading in English texts in English learning, to find out the factors influencing the failure of reading English texts in English learning, to find out how does the failure of reading English texts influence English learning process, to find out the ways of teacher to overcame failure of reading English texts in English learning among students. The result of the research are: The less time allocation of teaching and learning, The lack of students‟ self-confident in English learning because of the lack of vocabulary. The dominant factor influencing the failures of reading English texts in English learning are: the students‟ weak understanding of grammar and vocabulary. The teacher‟s effort to overcame reading failure are: asking the students to make exercise of English learning by working in groups, Asking the students to read English text and then asking the other students to scrutinize it. Keywords: Failure of reading ;English text ; English learning ; Teacher’s effort.